Preliminary Protein Profiling of Sodium Fluoride treated Lactobacillus acidophilus and Lactobacillus salivarius: Life Sciences-Microbiology for health care - Sandhyapriya Parthasaradhi; Chenchu Lakshmi Kandati; Jasti Pramoda Kumari (International Journal of Life Science and Pharma Research, 2022)
Sodium fluoride is a trace element required for human beings to prevent early dental disorders and to meet body’s minimum Fluoride levels. It is signified as a nutritional supplement for the prevention of dental caries in children of areas with inadequate Fluoride concentration in the drinking water. When Fluoride concentration exceeds required levels in the body, it commences bacteriostatic activity against beneficial flora in the gastrointestinal tract. Two such commonly affected organisms are L. acidophilus and L. salivarius. These are probiotic organisms that help to maintain immunogenic gut against several pathogenic organisms. In our previous study, Minimum inhibitory concentration (MIC) and growth dynamics were assessed on L. acidophilus and L. salivarius, in the presence of different Sodium fluoride concentrations. L. acidophilus and L. salivarius were observed to be inhibited at 20 mM and 40 mM Sodium fluoride concentrations respectively. These inhibitory concentrations were selected for further analysis. The proteins were isolated from such Sodium fluoride treated and untreated cells, the protein concentration was estimated by Bradford assay and protein profiling was done by 1D Gel Electrophoresis. The protein concentration is found to be higher in Sodium fluoride untreated organisms and below 3 kDa proteins of Sodium fluoride treated samples. Whereas low protein concentration was observed in the above 3 kDa protein samples (L.acidophilus treated protein sample above 3 kDa and L.salivarius treated protein sample above 3 kDa) of fluoride treated organisms. L. acidophilus and L. salivarius showed difference in protein expression under fluoride stress. Protein expression is high in L. salivarius than L. acidophilus. This is an indication that these strains have different capabilities for adapting to varying environmental conditions. we conclude that there is no impact on below 3 kDa protein samples in Sodium fluoride treated organisms and impact was there on the above 3 Kda proteins which are inhibited.